Concept note for national policy hubs under Ukama Ustawi - Ires, Idil (International Water Management Institute (IWMI), 2022)
National policy hubs aim to improve the enabling institutional and policy environment to guide climate-resilient agricultural transition in ESA. Specific hub activities can be described as the 4Ds (diagnose, design, develop, and deploy). Policy hubs diagnose the needs and knowledge gaps related to sustainable intensification and diversification of maize -mixed farming, de-risking through digitized agro-advisory services, agribusiness, empowerment, and multilevel scaling by aggregating research-based findings from the work packages and partners of Ukama Ustawi Initiative. This step is followed by designing and developing multistakeholder dialogues to communicate these findings with stakeholders, and consequently, informing policymaking and implementation on this basis. The first dialogue takes place in Zambia in August 2022, followed by Kenya and Zimbabwe. Finally, the hub will guide governments and other partners to deploy policies and strategies and follow up with policymaking and implementation through effective monitoring and evaluation mechanisms.